2015
DOI: 10.13189/ujer.2015.031117
|View full text |Cite
|
Sign up to set email alerts
|

An Insight into a School's Readiness to Implement a CAPS Related Indigenous Knowledge Curriculum for Meteorological Sciences

Abstract: This paper looks at those aspects of Indigenous Knowledge (IK) that are socially and culturally relevant in South Africa for teaching meteorological science concepts in a grade 9 geography class room using dialogical argumentation as an instructional model (DAIM). Focusing on the Western Cape Province, and using a quasi-experimental research design model, the study employed both quantitative and qualitative (mixed methods) to collect data in a public secondary school in Cape Town, in the Western Cape Province.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
0
3
0
3
Order By: Relevance
“…Figure 4 Others not included in the above categories All but one of the programs have multiple features in terms of approaches they adopted. One quasi-experimental study [36] reported the impact of dialogical argumentation instructional strategy on Indigenous students' science learning by comparing students' performances in the experimental and controlled groups. This study was assigned only one code (i.e., dialogical/communicative focus).…”
Section: Features Of the Program Practicementioning
confidence: 99%
“…Figure 4 Others not included in the above categories All but one of the programs have multiple features in terms of approaches they adopted. One quasi-experimental study [36] reported the impact of dialogical argumentation instructional strategy on Indigenous students' science learning by comparing students' performances in the experimental and controlled groups. This study was assigned only one code (i.e., dialogical/communicative focus).…”
Section: Features Of the Program Practicementioning
confidence: 99%
“…The application of realism theory for contextual understanding of socio-economic development and meteorology in particular in today's reality of climate change is gaining prominence in Africa and elsewhere. The realistic view and application of meteorological IKS have been incorporated in the ecological disaster early warnings strategies of some of the local authorities in Kenya (Liang, 2017), desertification and range ecology framework in Morocco (Davis, 2004), agricultural systems in northern Malawi (Moyo, 2010), policy advocacy for inclusion of IKS in meteorological sciences curricula in South Africa (Riffel, 2015) and linkages of conventional and IKS in weather forecasting in Zaka District of Zimbabwe (Makwara, 2013). The realization that IKS is central in meteorology and climatology has been aptly expressed by Mahony and Caglioti (2017) who retorts that "… new scholarship is showing more directly how the conduct of meteorology and climatology is deeply entangled with society [local community knowledge systems]" (Mahony & Caglioti, 2017).…”
Section: Theoretical Underpinning: Realism Theorymentioning
confidence: 99%
“…Os estudos internacionais que tivemos acesso não são diferentes. Ressaltamos agora a apresentação de outros estudos para referenciarmos as possibilidades metodológicas de avanço de pesquisas e de formação de professores e estudantes, são estes: Morawski & Budke (2019), Morgan (2006), Riffel (2015), Roberts (2013), Sutter et al (2019) e Uhlenwinkel (2017).…”
Section: Argumentação No Ensino De Geografiaunclassified
“…Uma outra pesquisa, agora originária da África do Sul (Riffel, 2015) teve como objetivo compreender quais os conhecimentos aborígenes são culturalmente relevantes para o ensino de ciências meteorológicas em um contexto usando um modelo instrucional baseado em argumentação, nomeado de DAIM (Dialogical Argumentation Instructional Model). O público alvo da pesquisa foram estudantes do 9º ano de uma escola na Cidade do Cabo e o material analisado foram os resultados obtidos da aplicação de pré-teste e pós-teste sobre conceitos de meteorologia.…”
Section: Argumentação No Ensino De Geografiaunclassified
See 1 more Smart Citation